A portable method of eliciting respect for social norms - Kimbrough, Erik O.; Vostroknutov, Alexander (Economics letters, 2018)
Recent models of prosociality suggest that cooperation in laboratory games may be better understood as resulting from concern for social norms than from prosocial preferences over outcomes. Underlying this interpretation is the idea that people exhibit heterogeneous respect for shared norms. We introduce a new, abstract task to elicit a proxy for individual norm-following propensity by asking subjects to choose from two actions, where one is costly. We instruct subjects that “the rule is” to take the costly action. Their willingness to incur such a cost reveals respect for norms. We show that choices in this task are similar across five countries. Rule-following is correlated with norm-consistent behavior in dictator games, providing support for our interpretation. •People exhibit heterogeneous respect for shared norms.•We introduce an abstract task to measure an individual’s norm-following propensity.•Choices in this task are similar across five countries.•Norm-following propensity is correlated with norm-consistent behavior in dictator games.